Phronesis: Recognising a neglected dimension of knowledge within occupational therapy research - Aileen Bergström; Margarita Mondaca; Ingeborg Nilsson; Susanne Guidetti; Lena Rosenberg (Scandinavian Journal of Occupational Therapy)
Background Phronesis is a way of knowing, implying wisdom, experiences, and reflections that guide our judgements. Phronesis, important for learning, is a neglected form of knowledge when applied to research.Aim To examine how phronesis is conceptualised and practiced in three research projects.Method Data from eight interviews with researchers involved in three research projects was generated. The interview material was analysed. A theoretical matrix of contemporary understanding of phronesis was applied to the material.Result Examples of phronesis from three research projects in occupational therapy are presented according to categories of contemporary phronesis; acknowledging embodiment, embracing humility, using perceptiveness, and practicing reflexivity.Significance This unique approach of analysing research projects contributes to the understanding of phronesis and its implications for research, providing valuable insights into the researchers’ praxis in their respective projectsConclusion There is a need for a greater recognition of phronesis as a dimension of knowledge within all types of research, and within the discipline. By not recognising phronesis as a legitimate form of knowledge, the discipline perpetuates a superiority of knowledge from episteme that dominates our ways of learning about the world around us and where the type of knowledge gleaned from phronesis is consequently marginalised.